Static Balance in Patients with Vestibular Impairments: A Preliminary Study - Hossein Talebi; Mohammad Taghi Karimi; Seyed Hamid Reza Abtahi; Niloofar Fereshtenejad (Scientifica)
Aims. Vestibular system is indicated as one of the most important sensors responsible for static and dynamic postural control. In this study, we evaluated static balance in patients with unilateral vestibular impairments. Materials and Methods. We compared static balance control using Kistler force plate platform between 10 patients with unilateral vestibular impairments and 20 normal counterparts in the same sex ratio and age limits (50±7). We evaluated excursion and velocity of center of pressure (COP) and path length in anteroposterior (AP) and mediolateral (ML) planes with eyes open and with eyes closed. Results. There was no significant difference between COP excursions in ML and AP planes between both groups with eyes open and eyes closed (p value > 0.05). In contrast, the difference between velocity and path length of COP in the mentioned planes was significant between both groups with eyes open and eyes closed (p value < 0.05). Conclusions. The present study showed the static instability and balance of patients with vestibular impairments indicated by the abnormal characteristics of body balance.